Russia's Vision of the Belt and Road Initiative: From the Rivalry of the Great Powers to Forging a New Cooperation Model in Eurasia. Issue 5 (September 2017) - Timofeev, Ivan; Lissovolik, Yaroslav; Filippova, Liudmila
Abstract: The article aims to highlight Russian approaches to Chinese One Belt‐One Road initiative. It examines possible opportunities and challenges for co‐development of the Eurasian Economic Union and the Belt project. Both projects and their co‐development may reduce the uncertainty in Eurasia, caused by significant structural changes in international relations and the world economy, the emergence of new trade regimes and the erosion of leadership in international affairs. Russian interests in this regard are determined by the need for modernization and long‐term development, which could also help to address acute security issues. These particular factors encouraged Russia to come up with an ambitious plan of the Extensive Eurasian Partnership, although the prospects of its implementation currently are uncertain. The present article argues that the success of Russia‐China collaboration in Eurasia will depend crucially on the future dynamics of the Eurasian integration, as well as on the agreement to co‐develop the Eurasian Economic Union and the Belt Initiative with concrete and mutually beneficial projects.